Economic upheaval in the Gulf region - Marc Piazolo (Intereconomics, 1995)
The six countries of the Gulf Cooperation Council face similar economic and political problems: falling oil revenues, growing budget deficits and increased demands on their foreign resources, a one-sided economic structure and increased pressure by public opinion for political rights. Their approaches to finding solutions have varied. Will these approaches be adequate to exploit the economic potential of the region in the future? Improvements in certain areas give ground for optimism.
Keywords: 330